Navigating the Role of Workplace Happiness amid Employer Branding and Prosocial Behaviour among IT Professionals - Shetty, Prathika; Bharath, Sindu; P Nagesh; Nanjundeswaraswamy, T S (Journal of Cultural Analysis and Social Change, 2025)
The research aims to explore the nexus between Prosocial Behaviour(PSB) and Employer Branding (EB). Also attempts to study the role of Workplace Happiness (HF) in relationship amid PSB and EB. The research design has two folds. Firstly, the antecedents of study variables were explored and validated adopting Exploratory Data Analysis (using SPSS and AMOS). Secondly, the mediating effect of HF is studied with the help of multiple regression analysis, additionally confirmed with Sobel test. The data were collected from 480 IT professionals working in Bangalore, India via email-based survey. The results indicate that prosocial behaviour impacts on employer branding. The HF is directly associated with EB while, PSB positively influences HF. Also HF mediates the nexus amid PSB and EB. The study offers vital and actionable insights for HR practitioners by deepening the knowledge of PSB and HF which enables in design and development of comprehensive HRM framework emphasizing value-based recognition programs and internal communication strategies that reinforce collective organizational identity. The outcome helps for orienting the employees towards PSB which guides their decision making process by encouraging them to balance between affective/emotionality (compassion, empathy, and interpersonal sensitivity) and cognitive/rationality (strategic thinking) as they must co-exist in contemporary workplaces. This dual emphasis fosters inclusive and psychologically safe work cultures, aligning with modern policy initiatives on workplace wellness. This study contributes by bridging the existing gap through investigating HF role in relationship amid PSB and EB.